THU0170 Adherence To Parenteral Methotrexate in Rheumatoid Arthritis Is Not A Major Issue and Does Not Influence The Occurrence of Major Cardiovascular Events. (15th July 2016) - Todoerti, M.; Carrara, G.; Olivieri, I.B.; Scirè, C.A.; ,
Abstract : Background: Cardiovascular (CCV) burden in rheumatoid arthritis (RA) is well defined. Several studies showed benefits from methotrexate (MTX) in reducing overall CCV morbidity and mortality [1]. Thus, MTX adherence could be crucial not only to achieve its disease modifying properties on articular signs and symptoms, but also to maximize long-term disease-related outcomes, including major CVV events. Objectives: To explore the impact of MTX adherence on the occurrence of hospitalized major CCV events in real life RA patients while persisting in MTX medication. Methods: Data including demographics, drug delivery, out-patient services and hospital admissions were extracted from health care administrative databases of the Lombardy Region (Italy) for the period between 1/1/2004 and 31/12/2013. Patients with RA were identified by a validated algorithm [2]. RA patients with a new course of treatment with parenteral MTX (new users) and at least 12 months of persistence were included. Hospitalizations/deaths for CCV events (acute myocardial infarction, stroke, heart failure) were evaluated through the Hospital Discharge Forms based on relevant ICD-9CM codes. The association between adherence to MTX - calculated as Proportion Days Covered (PDC) ≥80% - and risk of hospitalization for CCV event was assessed by survival models for competing risks. The results are presented as hazard ratios (HR) and 95% CI, crude and adjusted for sex, age, disease duration, Charlson comorbidity index, concomitant use of corticosteroids, NSAIDs, biologic disease modifying anti-rheumatic drugs/bDMARDs and combination of conventional synthetic DMARDs/csDMARDs. Results: A total of 5337 RA patients [F 3629, 68%; mean age (SD) 62.78 (12.7) years] were included in the analysis. Patients were mainly early onset RA [4015 (75%) <1 year disease duration], generally taking MTX as monotherapy [29 (1%) and 1218 (23%) patients on concomitant bDMARDs and non-MTX csDMARDs, respectively] in association with corticosteroids [3055 (57%)] and NSAIDs [2037 (38%)]. Mean (SD) Charlson comorbidity index was 1.34 (0.83). Most patients [4284 (80%)] resulted adherent to MTX. During 17.104 patient-years of observation, 440 hospital admissions due to major CVV events were registered (344 in adherent versus 96 in non adherent patients). Adherent vs non adherent patients did not significantly differ in the occurrence of CVV events (HR 0.82 CI95% [0.66–1.04]) causing hospital admission, even after adjusting for confounders (Table). Conclusions: In a cohort of real life RA patients from Italy, adherence to parenteral MTX is very high and does not significantly affect the occurrence of major CVV events, even after taking into account potential confounders. These results suggests persistent use of MTX, beside the adherence to it, still carries benefits in preventing from CCV events and that the parenteral administration route of MTX fosters adherence to treatment in RA. References: Marks JL, et al. Ther Adv Musculoskel Dis 2012. Carrara G, Scirè CA, Zambon A, et al. BMJ Open 2015. Disclosure of Interest: None declared